Answer:
There are three terms in the expanded form of the given polynomial expression [tex](-6m-n)^2[/tex] equivalent to the expression [tex]36m^2+12mn+n^2[/tex]
Therefore [tex](-6m-n)^2=36m^2+12mn+n^2[/tex]
Step-by-step explanation:
Given expression is [tex](-6m-n)^2[/tex]
To simplify the given expression as below:
[tex](-6m-n)^2[/tex]
[tex]=((-6m)+(-n))^2[/tex]
(Using the property [tex](a+b)^2=a^2+2ab+b^2[/tex])
Here a=-6m and b=-n
[tex]=(-6m)^2+2(-6m)(-n)+(-n)^2[/tex]
[tex]=6^2.m^2+12mn+n^2[/tex]
[tex]=36m^2+12mn+n^2[/tex]
[tex](-6m-n)^2=36m^2+12mn+n^2[/tex]
Therefore [tex](-6m-n)^2=36m^2+12mn+n^2[/tex]
There are three terms in the expanded form of the given polynomial expression [tex](-6m-n)^2[/tex] equivalent to the expression [tex]36m^2+12mn+n^2[/tex]